2016
DOI: 10.1139/cjb-2015-0124
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality affects phytotoxic potential of five native species of Neotropical savanna

Abstract: Phytotoxic secondary metabolites produced by plants have been studied as possible sources of bioherbicides. However, several environmental factors can change the secondary metabolism of plants, and thus, the production of these compounds. Among these factors, seasonality can be a source of variation in the content of all classes of secondary metabolites. In this study, we evaluated the phytotoxic effect of aqueous extracts of leaves from Byrsonima intermedia A. Juss. (Malpighiaceae), Gochnatia polymorpha (Less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…Triterpenes also act as lettuce germination inhibitors, but the mechanism of action of these compounds is still unknown (Martins et al 2010). In addition, the delay or reduction in germination by phytotoxicity can be explained by the effects on the mobilization of reserves, which occurs in the initial stages of seed germination, by the action of secondary metabolites (Pinto and Kolb 2015;Puig et al 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Triterpenes also act as lettuce germination inhibitors, but the mechanism of action of these compounds is still unknown (Martins et al 2010). In addition, the delay or reduction in germination by phytotoxicity can be explained by the effects on the mobilization of reserves, which occurs in the initial stages of seed germination, by the action of secondary metabolites (Pinto and Kolb 2015;Puig et al 2018).…”
Section: Resultsmentioning
confidence: 99%
“…They are used by the local population for the treatment of diarrhea, fever, mucosa infections and Chagas disease, presenting healing, antiseptic, antimicrobial, antihemorrhagic and anti-inflammatory properties (Guilhon-Simplicio and Pereira 2011; Moreira et al 2011;Saldanha et al 2016). It produces secondary metabolites in fruits, leaves, and also on the stem bark, such as volatile compounds, glycolipids, triterpenes, saponins, tannins and proanthocyanidins (Figueiredo et al 2005;Rodrigues 2007;Gonçalves et al 2013;Pinto and Kolb 2015;Arroyo et al 2018). The production of secondary metabolites can influence the ecological aspects of the place, the growth and development of other plants and organisms, in a phenomenon known as allelopathy.…”
Section: Introductionmentioning
confidence: 99%
“…Corroborating our observations, Gatti et al (2014) showed that Cerrado plant species presented the greatest phytotoxic potential with extracts obtained from specimens collected during the dry season. Pinto & Kolb (2016) observed that using extracts from ve Cerrado species obtained from specimens collected after the dry season or during the wet season presented greater phytotoxic e ects, and Murakami et al (2009) showed that extracts from leaf samples did not show variation in allelopathic potential between any of the four seasons.…”
Section: Discussionmentioning
confidence: 99%
“…One of the studies that screened for phytochemical content of the aqueous extract of M. chamissois leaves (AEMC) found that it was composed of Boletín Latinoamericano y del Caribe de Plantas Medicinales y Aromáticas/ 429 anthraquinones, triterpenoids, saponins, and tannins. This extract was phytotoxic to the germination of maize and cucumber, and the authors related the effect to the increase in triterpenoids and tannins content during the dry season (Pinto & Kolb, 2016). Alves (2016) described groups of compounds from M. chamissois extract, such as steroids, triterpenoids, flavonoids, saponins, tannins, alkaloids, and coumarins (Alves, 2016), and showed that M. chamissois extract demonstrated in vitro inhibition of MMP-2 and MMP-9 activities.…”
Section: Introductionmentioning
confidence: 99%